Indonesia - Accelerating Recovery in Uncertain Times : Brief for the Consultative Group in Indonesia - World Bank (Washington, DC, 2013)
The study reviews Indonesia's recovery so far, which in spite of only modest growth, is taking hold, and its base has expanded beyond consumption. With inflation under control, real wages are rising again, and poverty declined from a peak of over twenty three percent. The rapid export growth, and high oil prices were factors to offset capital outflows, thus, Indonesia's cushion of international reserves increased, lowering the deficit, and limiting financing needs, which resulted in bank, and corporate emergence. But financial markets were doubtful of the real economic developments, aggravated by political turmoil, and the developments in East Timor, which created market uncertainty. However, the study reflects optimism on the country's agenda, encouraged by the Government's program to accelerate recovery, with broad domestic and international support. The study examines policy options for fiscal sustainability, and the role of donors, and, assesses poverty within a constructive strategy for the future, exploring as well governance improvement through legal and judiciary reforms, suggesting the rule of law is still far from being assured. The study recommends changes within the political process, and to its legal system and civil service, as well as changes from the role of the military, to the way Government handles its finances.